Effect of knee joint angle on ankle dorsiflexion active range of motion, in healthy young adults - 木村 和樹; 西倉 尊; 五十嵐 貴大 (Japanese Journal of Physical Therapy for Diabetes Mellitus, 2022)
【Background】The ankle joint plays a crucial role in basic movements, such as standing, sitting, or walking, and postural strategies. However, the range of motion (ROM) of the ankle joint may be affected by musculoskeletal and neurological diseases of the lower limbs, such as motor paralysis due to stroke or lumbar disc disease. Diabetic neuropathy is one such disease, characterized by an increased risk of developing foot lesions resulting in restricted ankle ROM. Therefore, the purpose of this study was to clarify the effect of the knee joint flexion angle on the ankle dorsiflexion active ROM.【Methods】The subjects were 17 healthy young adult males (17 dominant legs). The effects of the relationship between the knee flexion and the ankle dorsiflexion active ROM at the following five condition of knee flexion 0° (extension 0°), knee flexion 30°, 60°, 90°, and 120° were examined. The ankle dorsiflexion active ROM was measured. The joint angle was calculated using Image-J, for the analysis of images taken by a digital single-lens reflex camera. For comparing the active ROM of ankle dorsiflexion between each knee joint angle, Friedman test was used followed by the Bonferroni multiple comparison test.【Results】The ankle dorsiflexion active ROM was significantly restricted in the knee extension 0° compared with positions where the knee joint was flexed ≥60° (p value <0.05). Also, the ankle dorsiflexion active ROM was greater at 90°and 120°knee flexion than at 30° (p value <0.05).【Discussion】The change in the ankle dorsiflexion active ROM with increasing knee joint flexion angle is affected by the extensibility of the gastrocnemius muscle, a two-joint muscle, when the knee joint is flexed <60°. It is considered that factors other than the extensibility of the gastrocnemius muscle affect the expansion of the active ROM of the ankle dorsiflexion when the knee joint is flexed at ≥90°.